Development of Application for Tutorial on Computer Graphics Lesson for Student of Multimedia Technology Department Nakhon Pathom Rajabhat University - Sajjaboriboon, Thanyanan (Rajapark Journal, 2021)
The objectives of this research were 1) to develop the application for tutorial on a computer graphics lesson for student of the multimedia technology department, Nakhon Pathom Rajabhat University; 2) to evaluate the efficiency of this application; and 3) to compare the achievement of learner before and after learning with this application. The research tools were the application for a tutorial on computer graphics lesson for student of the multimedia technology department, Nakhon Pathom Rajabhat University, the questionnaire for the application quality, and the pre-test and post-test. The research sample was the first-year undergraduate student majoring in the multimedia technology department, Nakhon Pathom Rajabhat University who study in the computer graphics subject on semester 2/2563, consisted of 57 students from 2 classes were selected using cluster sampling of total 7 classes. Developing the application with the content related about photo retouching, text editing, and creating GIF animation. Collecting data from students accessing the application after studying via smartphones or tablets. The statistics used for data analysis were mean, standard deviation, and t-test dependent samples. The results were as follows: 1) the assessment of overall quality of content and production techniques was at the highest level; 2) the efficiency of this application was at 1.43 according to the Meguigans criteria; and 3) the learning achievement of learners after studying higher than before.